Damage identification by wavelet analysis of modal rotation differences. (April 2021) - Katunin, Andrzej; Araújo dos Santos, José Viriato; Lopes, Hernâni
Abstract: In this paper, a novel damage identification approach based on differences in modal rotation fields obtained from shearographic measurements of structures and post-processed with the 2D continuous wavelet transform-based algorithm is presented. It is shown that the baseline approach, which assumes analysis of differences in modal rotation fields, allows to improve the sensitivity of a method to damage, making it possible to identify smaller damage with respect to the baseline-free approach. Moreover, a new approach for the reduction of the boundary effect is presented, which allows for the improvement visualization of the resulting maps using the proposed damage identification method. The proposed method was tested with eight damage scenarios, which allowed to prove repeatability of the obtained results, as well as to define a detectability threshold which is on the level of 3.5% of the thickness reduction.